2001
DOI: 10.1063/1.1367906
|View full text |Cite
|
Sign up to set email alerts
|

Structure of boron nitride nanotubules

Abstract: We have used high-resolution transmission electron microscopy to resolve the [0001] projected basal plane structure and chirality relationships in boron nitride nanotubes. Evidence for tube growth along both 〈101̄0〉 and 〈112̄0〉 is found. Our results suggest that the 〈112̄0〉 (armchair) tubes form first. Subsequent growth can take the form of a 〈101̄0〉 (zig-zag) tube or additional armchair tubes. In both cases, the additional walls can be accommodated without the need for defect formation for circumferential tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…It is worth noting that the zig-zag atomic arrangement was also found to be dominant in B-doped C NTs. [117] The zigzag BNNTs were repeatedly observed by Terauchi et al, [94] Ma et al, [92,118] Demczyk et al, [114] and Lee et al [91] in BNNTs prepared via different synthetic routes. In spite of different helicity types sometimes determined in BNNTs, various authors did agree on a characteristic grouping of all chiralities around one sole orientation (no matter what it is).…”
Section: Atomic Order As Revealed By Electron Diffractionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is worth noting that the zig-zag atomic arrangement was also found to be dominant in B-doped C NTs. [117] The zigzag BNNTs were repeatedly observed by Terauchi et al, [94] Ma et al, [92,118] Demczyk et al, [114] and Lee et al [91] in BNNTs prepared via different synthetic routes. In spite of different helicity types sometimes determined in BNNTs, various authors did agree on a characteristic grouping of all chiralities around one sole orientation (no matter what it is).…”
Section: Atomic Order As Revealed By Electron Diffractionmentioning
confidence: 74%
“…However, in some experiments the authors observed arm-chair and zigzag configurations being nearly equally plausible. [111,114,115] Interestingly, theoretical predictions based on molecular dynamics calculations performed by Blase et al [99] favored the growth of arm-chair BN tubes rather than zig-zag ones, but the significant difference between experimental synthesis temperatures, 5000°C [58][59][60] and 1500-1700°C, [76][77][78][79][80][81][82][83][84][85][86] and that used for Blasé's calculations, ca. 2700°C, [99] should be taken into account.…”
Section: Atomic Order As Revealed By Electron Diffractionmentioning
confidence: 93%
“…The electric dipole moments of heteropolar tubes provide crucial information for understanding their structures, elementary excitations and phase behavior [16,17]. They are related, for example, with an assortment of new photogalvanic effects [11].…”
mentioning
confidence: 99%
“…Minimal lattice energy calculations suggest that zig-zag is the most favourable chirality for BN nanotubes. In addition, the zig-zag BN nanotubes were repeatedly observed by Terauchi et al [19], Ma et al [20,21], Demczyk et al [22] and Lee et al [23], prepared by different synthetic routes.…”
Section: Introductionmentioning
confidence: 73%